Chronotype and social support among student athletes: impact on depressive symptoms. (2nd September 2021) - Wills, Chloe; Ghani, Sadia; Tubbs, Andrew; Fernandez, Fabian-Xosé; Athey, Amy; Turner, Robert; Robbins, Rebecca; Patterson, Freda; Warlick, Chloe; Alfonso-Miller, Pamela; Killgore, William D. S.; Grandner, Michael A.
ABSTRACT: Previous studies have shown individuals with evening chronotype to have a greater likelihood for depression (self-reported and clinical ratings), especially in young adults. However, the mechanisms for this relationship remain unknown. Low levels of social support may be a plausible mechanism: young adults with evening chronotypes are awake when others are sleeping, which may lead to feelings of isolation or low support. This study examined links between chronotype, depression, and social support in relationship subtypes within a group of university student athletes. Data were obtained from 189 NCAA Division-I student athletes across all sports. Chronotype was assessed with the Circadian Energy Scale and ranged from −2 (definitely morning type) to +2 (definitely evening type). Depressive symptoms were assessed with Center for Epidemiological Studies Depression scale. Social support was assessed with the Multidimensional Scale of Perceived Social Support, which included subscales for Family, Friends, and Significant Other. A subscale for Team was created using the items from the Friends subscale (changing the word "friends" to "teammates"). Regression analyses adjusted for age, sex, and minority status. More evening chronotype was associated with higher reported depressive symptoms ( p = .018), lower overall perceived social support ( p = .001), and lower perceived social support specifically provided by family ( p < .0001), friends ( p < .0001), and teammates ( p = .014). However, more evening chronotype was associated with higher depressive symptoms for higher, but not lower perceived social support from significant other. Moreover, chronotype-by-support interactions on depressive symptoms were observed; the statistical relationship between chronotype and depression was evident only in those with low (but not high) social support from friends and teammates. These data suggest that having a more evening chronotype may be associated with social isolation, and decreased opportunities for interactions with friends and teammates. This may contribute to the long-standing circadian association seen with depression in college student-athletes. Interventions aimed at increasing university support networks may reduce the impact of depression in students self-identifying with later chronotypes and sleep schedules.